IDENTIFIKASI KANDUNGAN TANIN DAN SAPONIN HIJAUAN PAKAN TERNAK SAPI POTONG YANG DIGEMBALAKAN DI DESA MURA KECAMATAN BRANG ENE SUMBAWA BARAT - Agung Satria; Mashur; Candra Dwi Atma; Maratun Janah (JURNAL SANGKAREANG MATARAM, 2022)
Substitution of chemical anthelmintics with anthelmintics derived from plants needs to be considered, if proven to have an effect on mortality of the worm Haemonchus contortus, so that the negative impact can be anticipated. The purpose of this study was to determine the content of tannins and saponins in forage fodder (corn leaves, gamal leaves and odot grass) given to beef cattle in Mura Village, West Sumbawa Regency. This research was conducted in March-April 2022. Sampling of the three types of forage studied was carried out in Mura Village, Brang Ene District, West Sumbawa Regency. Analysis of tannin and saponoin levels was carried out at the Pharmacy Laboratory of Stikes Bhakti Husada Mulia Madiun using Ultra Violet-Visible Spectroscopy Spectrophoto meter. Each unit of sample prepared as much as 2500 grams of wet leaves. The results showed that the tannin content of corn leaf was 3.52%, gamal leaf was 16.29% and odot grass was 7.88%, while the saponin content of corn leaf was 9.19%; 15.1% of gamal leaves and 6.46% of odot grass. In conclusion, gamal leaves contain higher tannins than odot grass and corn leaves, while for saponins gamal leaves are higher than corn leaves and odot grass.